Design and optimization of honeycomb structure in dual-link mechanism for revolving two-wing doors - Guoqing Zhou; Li Yuan; Ruize Zhou; Youdong Xing (Scientific Reports)
Abstract This research puts forward a retractable dual-link mechanism to alleviate revolving two-wing doors collision risks. The mechanism is composed of three key parts: dual linkages, a base plate, and a connector. Through theoretical analysis and structural topology optimization with the goal of mass minimization, the existing constraints in traditional optimization methods that undermine structural integrity have been revealed. To resolve this issue, a trapezoid honeycomb structure has been designed as a substitute for the substrate. This design has achieved an 18.8% reduction in weight while preserving mechanical performance. Quasi-static compression tests and simulations have been employed to verify the energy absorption capacity and deformation characteristics of the honeycomb structure under significant impact loads. This comprehensive approach offers a novel solution for enhancing pedestrian safety.